Metabolic changes in children with idiopathic central precocious puberty after gonadotrophin-releasing hormone agonist therapy: a meta-analysis - Zhou, Bo; Qu, Xia; Wang, Jianhong; Xu, Qi; Zhang, Lili; Wang, Xi; Peng, Nan; Gu, Jialu; Zhang, Xiaoqian; Wang, Qiong; Niu, Wenquan; Wang, Lin (Frontiers in Pediatrics, 2025)
BackgroundWe aimed to assess the effects of gonadotrophin-releasing hormone agonist (GnRHa) therapy on metabolic changes by synthesizing results from clinical trials involving children with idiopathic central precocious puberty (ICPP).MethodsLiterature search, trial selection, data extraction and quality assessment were completed independently by two investigators. STATA software (version 14.1) was used for data analyses. Effect-size estimates are expressed as weighted mean difference (WMD) with 95% confidence interval (CI).ResultsThis meta-analysis was conducted based on 19 clinical trials and 1,553 ICPP children. Overall analyses showed that for body mass index standard deviation score (BMISDS), no significance was noted after administering GnRHa to children with ICPP (WMD: −0.08; 95% CI: −0.22–0.06; p = 0.269). Similarly, no significance was noted for total cholesterol (WMD: 1.94 mg/dl; 95% CI: −10.29–14.17; p = 0.756), triglyceride (WMD: −5.31 mg/dl; 95% CI: −26.92–16.29; p = 0.630) and low-density lipoprotein (WMD: −9.63 mg/dl; 95% CI: −40.09–20.83; p = 0.535). By contrast, a statistically higher high-density lipoprotein of 7.07 mg/dl after administering GnRHa to children with ICPP (95% CI: 3.00–11.14; p = 0.001). Subgroup and meta-regression analyses revealed that initial body weight, sample size, and age were significant sources of between-trial heterogeneity. There was a low probability of publication bias for above comparison, as indicated by Egger's tests.ConclusionsOur meta-analytical findings indicate that GnRHa treatment did not appear to increase BMI and lipid metabolism levels in children with ICPP, irrespective of obesity status at the time of initiation therapy.Systematic Review RegistrationPROSPERO (CRD42023410554).